Integrated chassis control for multi-axle vehicles: A comprehensive review - Phuman Singh, Amrik Singh; Megat Zakaria, Megat Sharifuddin; Mohd Aras, Mohd Shahrieel (Penerbit Universiti Malaysia Pahang, 2024)
Multi-axle vehicles (MAVs) are used to transport heavy loads, navigate challenging terrain, and perform specific tasks. However, designing vehicle control systems for such vehicles is challenging. MAVs, such as trucks, buses, military vehicles, and multi-purpose vehicles, require sophisticated control techniques to increase the stability and ride comfort of such vehicles.This paper provides a comprehensive review of standalone control systems and integrated control systems (ICSs) for the steering, driving/braking, and suspension systems of MAVs, with a particular focus on the optimal tyre force distribution (TFD) in ICSs for MAVs. It also discusses various objective functions and optimisation methods used for the TFD. The findings indicate that optimising TFD significantly improves the stability of MAVs. As such, future studies may consider examining optimising three-axis TFD for MAVs to further improve vehicle stability.